Trends and Prospects for Crypto Asset Trading in Indonesia - Saputra, Ade Rizki (Formosa Journal of Sustainable Research, 2024)
Crypto asset trading has become a global phenomenon that affects various aspects of finance, including in Indonesia. This study explores the trends and prospects of crypto asset trading in Indonesia, with a focus on factors influencing market growth, stakeholder perceptions, and implications for the future of the crypto asset market in Indonesia. Qualitative research methods were used to analyze data from interviews with industry experts, crypto market stakeholders, and regulators, as well as a review of official documents related to crypto market regulations and policies in Indonesia. The findings of this study show that the growth of crypto asset trading in Indonesia is driven by the rapid adoption of digital technology, economic factors and global trends. Although still faced with challenges such as regulatory uncertainty, varying perceptions from stakeholders, and the need for stronger infrastructure, the prospects for crypto asset trading in Indonesia remain bright